Incidence of Escherichia coli O157:H7 in Thailand - Sukhumungoon, Pharanai (Universiti Kebangsaan Malaysia, 2015)
Enterohemorrhagic Escherichia coli (EHEC) especially serotype O157:H7 is one of the important food-borne pathogens because it is able to produce crucial toxins Shiga. However, the outbreak of this organism in Thailand has not been reported. Antibody to O157 antigen was detected in some Thai populations and Shiga toxin-producing E. coli were detected in low numbers of clinical specimens. Interestingly, some E. coli that showed positive to O157 fimbriae probe and lack of virulence gene were isolated from certain patients and one isolate of E. coli O157:H7 which possessed stx1, stx2v was detected in a normal child. In addition, the incidence of E. coli O157:H7 strains were monitored by the samples from cattle and retail beef in Thailand although their inability to produce toxins or produce in a low concentration was demonstrated. This review discusses the incidences of E. coli O157 in clinical and environmental samples of Thailand including the transmission possibility of this bacterium across the Thai border through food trade.